The american newspaper - Pope, Horace Greeley (My University, 1894)
Introduction: One of the most important principles emaciated by the Constitution of these United States was that there should be freedom of speech and freedom of the press. What does this “freedom of the press” mean? One thing it most assuredly does mean, and that is, censorship such as the Russian Government practices, shall never be allowed. That “liberty to know, to matter, and to argue freely, according to conscience,” which Milton prized above all liberties, most certainly belongs to the conquests of modern mind. This does not mean, however, that the press shall have unlicensed freedom in malicious attacks upon persons or institutions. Such restrictions must be practiced as are necessary for the preservation of society. Everwyehre you may happen to go in this whole country, you will find the church, the free-reading room, the school, and the newspaper as the great civilizing influences. In contrast to these are the degrading low theatres, gambling hells, and the saloon.
Citation: Pope, Horace Greeley. The american newspaper. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Newspaper; Freedom of Press; Press; Printing; United States; Theses; Manuscripts (documents)